Daleč doma Migracije iz Ljudske republike Kitajske v Slovenijo - Bofulin, Martina (Migracije, 2016)
Martina Bofulin offers a fine-grained analysis of complex relationships, practices and representations of Chinese migrants from Qingtian who live in Slovenia, but maintain active and manifold ties with their place of origin in southeast China as well as with friends and family living in Europe and beyond. Through her intensive multi-sited ethnographic research she reveals the opportunities and constraints at both ends of migration process that shape the everyday experiences of this group. The book ('Home and away: Chinese migration to Slovenia') goes beyond the mechanistic explanations of migration pull and push factors and describes a complex mix of migration regimes, discursive spaces, forms of consumption, family practices and individual imaginations blurring the line between home and away.